2019
DOI: 10.1308/rcsfdj.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

A cost analysis of non-surgical extractions in primary versus secondary care

Abstract: It has been well established that the secondary care sector often receives high volumes of referrals for extractions from general dental practitioners (GDPs). 1 This has a significant financial impact for the NHS as secondary care costs are higher than in the primary care sector. 2 , 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…(3) In addition, there are significant financial implications for carrying out routine extractions in secondary care when compared to primary care. (4) Since NHS England published the 'Five Year Forward View' in 2014 there has been a focus on implementation of Managed Clinical Networks (MCNs) across the entirety of the NHS to improve the provision of services. (5) MCNs provide a structured healthcare pathway to integrate care locally, improve quality and access to care, reduce health inequalities and ultimately improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…(3) In addition, there are significant financial implications for carrying out routine extractions in secondary care when compared to primary care. (4) Since NHS England published the 'Five Year Forward View' in 2014 there has been a focus on implementation of Managed Clinical Networks (MCNs) across the entirety of the NHS to improve the provision of services. (5) MCNs provide a structured healthcare pathway to integrate care locally, improve quality and access to care, reduce health inequalities and ultimately improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a sustained increase in referrals from primary care dental practices into dental hospital services for dental surgery procedures, and it has been established that this contributes to significant pressures on National Health Service (NHS) finances due to higher costs in secondary care than in the primary care sector [ 1 , 2 ]. An assessment of English oral surgery services, demonstrated that in a 3-year period from 2004, minor oral surgery referrals doubled from a monthly average of 182 to 364 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%